Global research trends on 4D in education using bibliometrics analysis techniques - Fajar Rizky, Muhammad Rafi; Suparman, Suparman (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
The 4D development model is a development model that has systematic stages of activity consisting of define, design, development, and disseminate. However, in the range of 2000 to 2023, there is still little analysis that discusses global research trends on 4D in education. Therefore, the purpose of this research is to find out the global research trend about 4D in the field of education. This research method uses descriptive quantitative methods using bibliometric analysis. The data source used is publication data extracted from the dimensions database. The results of this study show that 4D topics in education will become a trend in the future. This can be seen from the results of VOSviewer visualization which shows that there are still many novelties that can be discussed in the topic. The limitation in this study is that it is only limited to using the Dimensions database. Therefore, further research is needed on 4D topics in education from other databases and is carried out regularly to see the development of 4D topic trends in education